Auriculotherapy for sleep quality in people with primary insomnia: A protocol for a systematic review and meta-analysis. Issue 8 (February 2019) - Ren, Runyuan; Zhang, Jiayuan; Zhang, Tingting; Peng, Yangzhi; Tang, Chenjian; Zhang, Qi
Abstract: Background: Primary insomnia is one of the common sleep disorders. Auriculotherapy originated from traditional Chinese medicine, has been thought as a promising treatment for primary insomnia. We aim to evaluate the efficacy and safety of auriculotherapy for patients with primary insomnia through this systematic review. Methods: Five English databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, AMED, and CINAHL), 4 Chinese databases (CBM, CNKI, CQVIP, and Wanfang), and 5 clinical trial registration databases (ClinicalTrials.gov, ANZCTR, EU-CTR, ChiCTR, and ICTRP) will be searched from establishment of the database until November 2018. Articles written in English or Chinese languages will be included. The randomized controlled trials of auriculotherapy (auricular acupuncture and auricular acupressure) for patients with primary insomnia will be included. The primary outcome will be assessed according to the Pittsburgh sleep quality index. Meta-analysis will be conducted with the use of RevMan 5.3. The specific process will refer to the Cochrane Handbook 5.1 for Systematic Review. Results: High-quality synthesis of current evidence on the efficacy and safety of auriculotherapy for primary insomnia will be provided in this study. Conclusion: This systematic review aims to present evidence for whether auriculotherapy is an effective intervention which can improve sleep quality in patients suffering primary insomnia. PROSPERO registration number: CRD42019106422.